2015
DOI: 10.1097/ta.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in hospitalization and in-hospital mortality associated with traumatic brain injury in Canada

Abstract: Background: Traumatic brain injury (TBI) is the leading cause of traumatic death and disability worldwide. We examined nationwide trends in TBI-related hospitalizations and in-hospital mortality between April 2006 and March 2011 using a nationwide, population-based database that is mandatory for all hospitals in Canada. Methods: Trends in hospitalization rates for all acute hospital separations in Canada were analyzed using linear regression. Independent predictors of in-hospital mortality were evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…Mathias and Wheaton (2015) demonstrated that elderly patients have less brain reserve and greater vulnerability that amplify brain damage and limit functional recovery. Moreover, Fu et al (2015) found that the severity of lesions, the number of MCs, and older age are the most important predictors of intra-hospital mortality in these patients. Again, other clinical factors could unpredictably influence patients' clinical evolution, such as the presence of ischemic or organic heart diseases (Pistoia et al, 2015) or altered brain activity (Sarà et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Mathias and Wheaton (2015) demonstrated that elderly patients have less brain reserve and greater vulnerability that amplify brain damage and limit functional recovery. Moreover, Fu et al (2015) found that the severity of lesions, the number of MCs, and older age are the most important predictors of intra-hospital mortality in these patients. Again, other clinical factors could unpredictably influence patients' clinical evolution, such as the presence of ischemic or organic heart diseases (Pistoia et al, 2015) or altered brain activity (Sarà et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…One of the main nuisance factors affecting functional recovery from severe TBI is the presence of medical complications (MCs; Ganesh et al, 2013;Whyte et al, 2013;Pistoia et al, 2015). The presence of one or more MCs is associated with increased hospitalization time, worsened functional outcome, and increased mortality (Fu et al, 2015;Chan et al, 2017). Generally, these disorders are directly related to paroxysmal sympathetic hyperactivity (Lucca et al, 2019) or epileptic seizures (Pascarella et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, Fu et al [22] reported stable hospital admission rates for children and young adults over the period 2006-2010 but did report an increase of TBI in elderly adults. In the United States, Coronado et al [3] reported an increase in the number of emergency department and outpatient department visits, but no change in hospital admission rates over the period 1995-2009.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of hospitalization among older adults (≥ 65 years of age) with traumatic brain injury (TBI) has increased by 24% over the past decade [1]. On average, older adults with TBI are hospitalized four times as often, have longer hospital stays [2], and experience slower recovery trajectories and worse functional outcomes compared to younger populations with the same injury severity after TBI [3].…”
Section: Introductionmentioning
confidence: 99%